Integrating Bottom-up and Top-down Approaches in Tanzania's Climate Change Adaptation Planning: Exploring Their Impact on Adaptive Capacity in Adaptation Projects. - Sumari, Beatrice Kundael; Pauline, Noah; Bwanduruko Mabhuye, Edmund (Journal of Development Studies, 2025)
The purpose of this article is to investigate the influence of planning methodologies, specifically the distinctions between top-down and bottom-up approaches, on the adaptive capacity of climate change adaptation projects. Despite the prevalence of both approaches in Tanzania, there remains a lack of understanding regarding the differences in project's adaptive capacity between projects executed under each methodology. To address this gap, the study conducts an in-depth evaluation of four adaptation projects in the Arusha region, Tanzania. The study utilises a theoretical framework based on Structure and Agency by Antony Giddens (1976) and qualitative data derived from focus group discussions, interviews, and field observations. Our findings reveal significant disparities between projects executed under top-down and bottom-up approaches. Projects guided by top-down methodologies, typically led by central government agencies, often result in maladaptive outcomes due to their one-size-fits-all approach. In contrast, the bottom-up planning approach empowers communities with greater agency, leading to heightened adaptive capacity, though the approach still faces challenges. Based on these findings, the study recommends prioritizing bottom-up approaches for future initiatives in Tanzania. By empowering communities and enhancing their agency in project decision-making, these approaches can foster greater adaptability to climate change challenges.